2019
DOI: 10.9734/jsrr/2019/v23i130112
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Sexual Maturity of Threadfins Polydactylus quadrifilis (Cuvier, 1829), Galeoides decadactylus (Bloch, 1795) and Pentanemus quinquarius (Linné, 1758) of the Artisanal Marine Fishery of Grand-Lahou (Ivory Coast)

Abstract: Reproduction of the threadfins of the costal shelf of Grand-Lahou was studied with a monthly sampling frequencies range from may 2009 to april 2011. 534 specimens of Polydactylus quadrifilis, composed of 315 males and 219 females and 648 Galeoides decadactylus composed of 420 males and 228 females, then 453 individuals of Pentanemus quinquarius composed of 210 males and 243 females were used. The sexual maturity parameters of threadfins fishes indicate a size of first maturity (L50 = 67.5 cm) for females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
3
0
0
Order By: Relevance
“…Further, the present study indicated long-overdue first sexual maturity in both sexes of the assessed stock (Female, L 50% = 50% L max; Male , L 50% = 35%L max ). A similar length at first sexual maturity observed for female specimens in the present study has been revealed for G. decadactylus (L 50% = 18.5 cm [24], but much lower value for both sexes has also been reported (L 50% <16 cm TL: [20,25,26] .…”
Section: Discussion 41 Spawning Indicatorssupporting
confidence: 88%
See 2 more Smart Citations
“…Further, the present study indicated long-overdue first sexual maturity in both sexes of the assessed stock (Female, L 50% = 50% L max; Male , L 50% = 35%L max ). A similar length at first sexual maturity observed for female specimens in the present study has been revealed for G. decadactylus (L 50% = 18.5 cm [24], but much lower value for both sexes has also been reported (L 50% <16 cm TL: [20,25,26] .…”
Section: Discussion 41 Spawning Indicatorssupporting
confidence: 88%
“…Results statistically portrayed numerical gender equality in the population of G. decadactylus owing to the insignificant deviation (p>0.05) of the observed sex ratio from the hypothetical ratio of 1:1 in spite of the colossal gap in the female: male sex ratio of 1:1.8. A similarly biased female: male sex ratio has been observed for the study species (F: M, 1:1.8; 1:1.27; 0.46:1) [20,21,22] . Major spawning in G. decadactylus may be occurring in October owing to high GSI relative to increased liver weight (HIS), and the species could be a partial spawner due to its protracted spawning behaviour (August through October).…”
Section: Discussion 41 Spawning Indicatorssupporting
confidence: 74%
See 1 more Smart Citation